Information seeking behaviours of rural women in Malaysia - Abu Bakar, Ahmad Bakeri (University of Nebraska--Lincoln Libraries, 2011)
This study examines the information needs and seeking behaviours of women in a rural setting of Malaysia The aim of the study is to identify the information needs of women, and to determine the information sources used by women in a rural village, to determine their information seeking behaviours and to identify any accessbarriers to those sources of information. A sample was selected and given a questionnaire. The return rate was 64 percent. The study revealed that respondents were concerned with information related to food and child education. When seeking information on food and child education, respondents used family or friends and popular magazines as the main sources. When seeking information on food and child education through the Internet most used relevant websites to get information. They also used the online periodicals or magazines. Generally they observed that their village lacks infrastructure, which impedes their success. They suggested the establishment of a mosque library with Internet facilities in their village as a short term solution to their problems.